An Oceanic Plateau Induced Subduction Zone Jump From Proto‐ to Paleo‐Tethys in East Kunlun, Northern Tibetan Plateau - Rutao Zang; Yunpeng Dong; Dazhi Jiang; Dengfeng He; Shengsi Sun; Bo Hui; Bin Zhang (Geochemistry, Geophysics, Geosystems, 2025)
Abstract The relationship between the Proto‐Tethys and Paleo‐Tethys is still debated. Some researchers believe that the Paleo‐Tethys opened after the Proto‐Tethys closed, while others argue that they are the same ocean with two stages of subduction. We present field geology, geochemical, and geochronological data to support the latter interpretation. We identified a typical oceanic plateau remnant in the East Kunlun Orogenic Belt, northern Tibetan Plateau. The remnant preserves voluminous pillow basalts overlain by limestones and breccias. The pillow basalts are characterized by slight enrichment of LILEs and HSFEs, which are similar to those of modern oceanic plateaus and were derived from 15% to 30% melting of a spinel lherzolite mantle source at a high potential temperature (±1,556°C) suggesting a mantle plume origin. The formation age of the oceanic plateau is determined by zircon U‐Pb dating to be 430 ± 3 and 428 ± 3 Ma. We suggest that the oceanic plateau jammed the subduction of the Proto‐Tethys and led the subduction zone to jump to a new location, which has been attributed to the subduction of the Paleo‐Tethys. This finding also explains the absence of magmatic activities in this region from 370 to 290 Ma.